Phylogenetic Analysis of the Kinesin Superfamily from Physcomitrella - Shen, Zhiyuan; Collatos, Angelo R.; Bibeau, Jeffrey P.; Furt, Fabienne; Vidali, Luis (Frontiers in Plant Science, 2012)
Kinesins are an ancient superfamily of microtubule dependent motors. They participate in an ex-tensive and diverse list of essential cellular functions, including mitosis, cytokinesis, cell polari-zation, cell elongation, flagellar development, and intracellular transport. Based on phylogenetic relationships, the kinesin superfamily has been subdivided into 14 families, which are represented in most eukaryotic phyla. The functions of these families are sometimes conserved between species, but important variations in function across species have been observed. Plants possess most kinesin families including a few plant-specific families. With the availability of an ever in-creasing number of genome sequences from plants, it is important to document the complete complement of kinesins present in a given organism. This will help develop a molecular frame-work to explore the function of each family using genetics, biochemistry and cell biology. The moss Physcomitrella patens has emerged as a powerful model organism to study gene function in plants, which makes it a key candidate to explore complex gene families, such as the kinesin superfamily. Here we report a detailed phylogenetic characterization of the 71 kinesins of the kinesin superfamily in Physcomitrella. We found a remarkable conservation of families and sub-family classes with Arabidopsis, which is important for future comparative analysis of function. Some of the families, such as kinesins 14s are composed of fewer members in moss, while other families, such as the kinesin 12s are greatly expanded. To improve the comparison between spe-cies, and to simplify communication between research groups, we propose a classification of subfamilies based on our phylogenetic analysis.